2010
DOI: 10.1007/s11274-010-0522-4
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of methyl tert-butyl ether by newly identified soil microorganisms in a simple mineral solution

Abstract: Methyl tert-butyl ether (MTBE) is a widely used fuel ether, which has become a soil and water contaminant. In this study, 12 microbial strains were isolated from gasoline-contaminated soils and selected because of their capacity to grow in MTBE. The strains were identified by 16S/ITS rDNA gene sequencing and screened for their ability to consume MTBE aerobically in a simple mineral solution. Solid phase microoextraction and gas chromatography were used to detect MTBE degradation. High levels of MTBE biodegrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Bacillus strains were also cultivated from oxygenate-contaminated sources in this study (Fig. 6a), as well as Kao et al (2010) and Barbera et al (2011); however, this may be due to spore resistance and longevity in groundwater.…”
Section: Resultsmentioning
confidence: 87%
“…Bacillus strains were also cultivated from oxygenate-contaminated sources in this study (Fig. 6a), as well as Kao et al (2010) and Barbera et al (2011); however, this may be due to spore resistance and longevity in groundwater.…”
Section: Resultsmentioning
confidence: 87%
“…Jose Barbera et al confirmed that E. cloacae species play an important role in the MTBE biodegradation. They also showed that E. cloacae MCM2/1 has a high potential for utilizing MTBE (39). In the first hours, degradation rate by K. planticola was higher than other strains, and it seems that E. coli needs more time for degrading MTBE (Figure 3), it can be due to the complex molecular structure of MTBE, while the cultures containing yeast extract, this compound makes a good condition for better growth of the strains (19).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic flexibility of these genera has been described in several studies, where degradation of organic pollutants was demonstrated (Ghosal et al, 2010;Ryan et al, 2009, Zhang et al, 2007. Some studies describe the complete aerobic degradation of MTBE (Barberà et al, 2011;Nipkey & Nipkey, 2006), but not its anaerobic degradation, because the accumulation of toxic tert-butyl alcohol may occur (Wei & Finneran, 2011).…”
Section: Discussionmentioning
confidence: 99%